STRUCTURAL EQUATION MODELING (SEM) DENGAN SMARTPLS DALAM MENYELESAIAKAN PERMASALAHAN DI BIDANG EKONOMI - Sayyida, Sayyida (Journal MISSY (Management and Business Strategy), 2023)
Structural Equation Modeling (SEM) is a statistical analysis tool that is widely used today. SEM is a multivariate analysis tool that allows to solve complex problems. There are several software developed to assist analysis using SEM. SmartPLS is software that is widely used in management research because it is able to solve complex problems without any normality assumptions. There are three stages of completion with SmartPLS software, namely making drawings, testing measurement models, and testing structural models. Drawings are made according to the conceptual framework and the hypothesized variable relationships. The measurement model test aims to test the validity and reliability of indicators. While the structural test aims to answer the research hypothesis. This paper is expected to help novice researchers overcome limitations or inability to use SEM analysis, especially using smartPLS software.